Increasing the Reliability of the Grading System for Voiding Cystourethrograms Using Ultrasonography: An Inter-Rater Comparison - Ozaydin, Seyithan (Nephrourol Mon, 2016)
BACKGROUND: To assess the effectiveness of the current vesicoureteral reflux (VUR) grading system according to the international classification of VUR (ICVUR) and to evaluate whether VUR grading accuracy could be improved by renal ultrasonography (RU) according to the Society for Fetal Urology (SFU) grading system. OBJECTIVES: Therefore, this study assessed the accuracy of the current VCUG staging system by assessing inter-rater reliability among pediatric radiologists and urologists; it also evaluated whether accuracy is increased by RU without consensus (with respect to VCUG grading). METHODS: Four pediatric urologists and four pediatric radiologists independently graded 120 voiding cystourethrograms (VCUGs). Middle VUR grades were divided into the following three groups: VUR consensus grade III (group 1), VUR consensus grade IV (group 3), and VUR non-consensus grades III and IV (group 2). All groups were compared with respect to hydronephrosis grade using RU. RESULTS: The intraclass correlation coefficient (ICC) values ranging from 0.86 to 0.89 reflected good reliability. The lowest agreement was associated with middle grades (III and IV). A marked difference in sensitivity was observed between groups 1 and 3 (35% and 95%, respectively, P < 0.05), indexed by SFU hydronephrosis grade, suggesting that VCUG cases in group 2 (n = 16 at SFU 0 or 1) could be accepted as grade III, and SFU scores of 2, 3, or 4 could be considered grade IV. CONCLUSIONS: Inter-rater accuracy could be improved at middle grades using renal ultrasonography (USG), which could promote communication between different specialists.